Simulated temperature of a tungsten spot facing large plasma heat loads - J. Moritz; S. Heuraux; M. Lesur; E. Gravier; F. Brochard; L. Marot; P. Hiret (Nuclear Materials and Energy)
In fusion devices like ITER, plasma-wall interactions are a significant concern due to the high heat fluxes, often tens of MW/m2, impacting the first wall. These intense heat fluxes can lead to the formation of hot spots on components facing the plasma, such as tungsten, used in divertor plates and antennas. This results in material erosion and plasma core contamination. Our study investigates the thermal behavior of tungsten surfaces under these conditions using fluid modeling and Particle-In-Cell (PIC) simulations. We examine the effects of thermionic electron emission on the sheath potential and heat transmission. The simulations reveal that thermionic emission can decrease the sheath voltage, increasing the surface temperature due to enhanced heat flux due to electrons. Additionally, we explore how the ratio between the spot size (S) and the surrounding surface length (Ly) influences the surface temperature. We find that a higher Ly/S ratio allows the surface to reach higher temperatures before the system enters the space-charge-limited regime, where thermionic current is maximized and considerably larger than the case where the entire surface is emissive (Ly=S).